2020
DOI: 10.1093/nar/gkaa541
|View full text |Cite
|
Sign up to set email alerts
|

Ctf18-RFC and DNA Pol ϵ form a stable leading strand polymerase/clamp loader complex required for normal and perturbed DNA replication

Abstract: The eukaryotic replisome must faithfully replicate DNA and cope with replication fork blocks and stalling, while simultaneously promoting sister chromatid cohesion. Ctf18-RFC is an alternative PCNA loader that links all these processes together by an unknown mechanism. Here, we use integrative structural biology combined with yeast genetics and biochemistry to highlight the specific functions that Ctf18-RFC plays within the leading strand machinery via an interaction with the catalytic domain of DNA Pol ϵ. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 83 publications
2
46
0
Order By: Relevance
“…A recent genome-wide analysis of PCNA occupation on the leading and lagging strands consistently showed that Ctf18-RLC preferentially loads PCNA on the leading strand, and that the RFC complex preferentially loads PCNA on the lagging strand 28 . This study, along with other studies, showed that interaction with Pol ε contributes to the recruitment of Ctf18-RLC to replication forks 28 , 29 . However, Ctf18 is not essential for bulk DNA replication and cannot substitute for Rfc1 deletion.…”
Section: Primary Roles Of the Rfc Complex And Rlcssupporting
confidence: 82%
See 2 more Smart Citations
“…A recent genome-wide analysis of PCNA occupation on the leading and lagging strands consistently showed that Ctf18-RLC preferentially loads PCNA on the leading strand, and that the RFC complex preferentially loads PCNA on the lagging strand 28 . This study, along with other studies, showed that interaction with Pol ε contributes to the recruitment of Ctf18-RLC to replication forks 28 , 29 . However, Ctf18 is not essential for bulk DNA replication and cannot substitute for Rfc1 deletion.…”
Section: Primary Roles Of the Rfc Complex And Rlcssupporting
confidence: 82%
“…Ctf18 mutants defective with Pol ε-binding were originally reported to be sensitive to hydroxyurea and defective in the replication checkpoint, as shown by reduced Rad53 phosphorylation 63 . On the other hand, two recent reports show that hydroxyurea sensitivity and reduced Rad53 phosphorylation are not observed in either Pol ε-binding-defective dcc1 mutants or Dcc1-binding-defective Pol ε mutants 28 , 29 . However, the same paper showed that Rad52 foci, markers for recombination, and Psf1 phosphorylation, a marker for late origin firing, both of which are normally suppressed by checkpoint activation, are increased in Pol ε-binding-defective ctf18 mutants treated with hydroxyurea.…”
Section: Primary Roles Of the Rfc Complex And Rlcsmentioning
confidence: 86%
See 1 more Smart Citation
“…Instead, we show that it is mediated by the binding of the RFC CTF18 to Polε ( Fig 6A ). Ctf18 was found to be in contact with Polε throughout the cell cycle [ 65 ], via the Dcc1 subunit of the RFC CTF18 complex. Mutating the conserved W736 and W740 residues [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the CTF18, CTF8, and DCC1 S. cerevisiae genes also have a very high number of SL interactions with mutations in GIS genes, scoring just below FEN1 in the analysis performed by Guo et al (6). The CTF18−CTF8−DCC1 complex prevents formation of single-strand gaps on the leading strand (15). Thus, mechanistically, the SL interactions observed in the context of mutations targeting the CTF18−CTF8−DCC1 complex may be very similar to those targeting FEN1.…”
Section: Exploiting Postreplication Gaps For Synthetic Lethalitiesmentioning
confidence: 97%